Study of heart rate recovery in diabetic women to predict the risk of cardiovascular disease - Yadav, Kritika D.; Gunjal , Sambhaji (International Journal of Research in Medical Sciences, 2023)
Background: Diabetes mellitus is characterized by rise in the level of glucose concentration. Diabetes increases the risk of heart attack by four times in women and two times in men. An attenuated HRR immediately after exercise is considered an index to identify silent autonomic dysfunction. Individuals with low values for HRV and HRR present a higher risk of cardiovascular outcome. Methods: 50 diabetic participants with a mean age of 54.52 and SD±8.63 years. All the participants were assessed for heart rate and blood pressure before the assessment and after the 3-minute YMCA step test. Post test heart rate was assessed immediately after 1, 2 and 3 minutes. Heart rate recovery was calculated by subtracting heart rate immediately after 3 minutes of test to heart rate after 1 minute. Results: 50 diabetic women with the mean age of 38.96 and SD±9.36, the age ranged from 20 to 50. The resting heart rate mean was 98.08 and standard deviation was ±9.82. Mean and SD of heart rate immediately after 3 minutes was 142.66 and SD was ±8.05 and after 1 min was 130.86 and ±7.84 respectively. The heart rate recovery mean was 11.8 and SD was ±4.25. Conclusions: Study concluded heart rate recovery is delayed in diabetic women and it is associated with increased risk of cardiovascular disease.